Mathematical Analysis of Diarrhea Model with Saturated Incidence Rate. - Musinguzi, Jason (Kabale University, 2024)
We present a compartmental mathematical model of (SITR) to investigate the effect of saturation treatment in the dynamical spread of diarrhea in the community. The mathematical analysis shows that the disease free and the endemic equilibrium points of the model exist. The disease-free equilibrium is locally and globally asymptotically stable when RO< I and unstable otherwise RO> I.